Reconceptualising transnational governance: Making global institutions fit for purpose - Seán Cleary (Kiel Institute for the World Economy (IfW), 2017)
Tensions between national democratic accountability and transnational challenges undermine trust and collective action. Asymmetry between an integrated global economy, fragmented global community, and defective global polity, causes social turbulence. Facing technological disruption, we need a new order to address inequality; transform education; and build social capital. Diplomatic exchanges will not suffice, but the Paris Agreement and Agenda 2030 were enabled by bottom-up deliberations. The author proposes a UN conference of states to decide how to balance environmental sustainability, economic development and human security, after consultations on national proposals between policymakers, business and civil society, on principles, underlying values and legal norms.
Keywords: F53; 330; national democratic accountability; international cooperation; institutional weakness; global order; technological disruption; planetary boundaries; inequality; social capital; asymmetry; integrated global economy; fragmented global community; defective global polity; environmental sustainability; economic development; human security; national consultations; values; legal norms